Efficient conversion of empty fruit bunch of oil palm into fertilizer enriched compost. - Siddiqui, Yasmeen; Meon, Sariah; Ismail, Mohd Razi; Rahmani, Mawardi; Ali, Asgar (EM International, 2009)
The microbial transformation of empty fruit bunches (EFB) of oil palm waste treated with chicken manure has utility for the improvement of plant growth. It is an adjunct to minimizing agro-waste disposal in a sustainable manner. Composting was carried out using a closed system provided with aeration. Toxicity of compost was determined by seed germination and plant growth assay. Different compost to peat combinations of 25:75, 50:50, 75:25 and 100% compost were used. Highest percentage of germination was obtained with 25% compost.